A normal diffusing capacity of the lungs for carbon monoxide is rare in incidental pulmonary arterial hypertension in systemic sclerosis: Data from the Pulmonary Hypertension Assessment and Recognition of Outcomes in Scleroderma cohort. Issue 3 (October 2018) - Overbury, Rebecca S; Murtaugh, Maureen A; Frech, Tracy M; Steen, Virginia D
Objective: Our purpose was to determine the frequency of normal diffusing capacity for carbon monoxide defined as ⩾70% predicted, in those diagnosed with pulmonary arterial hypertension in the Pulmonary Hypertension Assessment and Recognition of Outcomes in Scleroderma cohort. We compared those with normal diffusing capacity for carbon monoxide to those with reduced diffusing capacity for carbon monoxide <70% in order to better clarify the role of pulmonary function testing as a screening test for pulmonary arterial hypertension and to better understand this population. Methods: Entry criteria included a right heart catheterization with mean pulmonary artery pressure ⩾25 mm Hg and pulmonary capillary wedge pressure ⩽15 mm Hg. Demographics, echocardiogram variables, B-type natriuretic peptide levels, right heart catheterization findings, and survival were described for both groups. Results: Of (n = 202), 11 (5.4%) had a diffusing capacity for carbon monoxide of ⩾70% versus 191 (94.6%) who had a diffusing capacity for carbon monoxide <70%. There were no identified statistical differences between the groups. Left atrium size was 4.1 cm in the normal diffusing capacity for carbon monoxide patients compared to 3.7 cm in the low diffusing capacity for carbon monoxide group but did not reach statistical significance. There were no statistically significant differences in survival. On repeat testing, seven patients subsequently developed a diffusing capacity for carbon monoxide <70%. Conclusion: Pulmonary Hypertension Assessment and Recognition of Outcomes in Scleroderma data suggest that it is very rare for a patient to develop pulmonary arterial hypertension with a preserved diffusing capacity for carbon monoxide. The data support the importance of obtaining diffusing capacity for carbon monoxide and that a patient with a normal diffusing capacity for carbon monoxide while suspected to have systemic sclerosis-pulmonary arterial hypertension should be considered critically. Diffusing capacity for carbon monoxide >70% was present in too few patients to find significant differences in B-type natriuretic peptide and atrium size. Future research should seek to confirm abnormal B-type natriuretic peptide, increased left atrium size, and other evidence of myocardial involvement on diffusing capacity for carbon monoxide.